2002
DOI: 10.21608/jssae.2002.255935
|View full text |Cite
|
Sign up to set email alerts
|

Improving Water and N-Use Utilization for Field Crops via Lternate- Furrow Irrigation Echnique. 1-Maize Crop

Abstract: Two field experiments were executed at the farm of Gemmeiza Agric. Res. Stn. during 2001and 200 seasons, to find out the extent to which alternate-furrow irrigation technique, affected water and N-utilization for maize crop.Data revealed significant reductions in applied water, due to conveying the water through alternate-furrow irrigation at, 7 or 14 days interval. Increasing N-rate resulted in increased applied water values, under the adopted irrigation techniques , a similar trend was observed regardless ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…WP values increased by 11.3 % and 2.9 %, respectively, when the A1/1E10 regime was applied to the (EFI15) and (A1/1C10) treatments. Similar findings were reported by Abdel-Maksoud et al (2002) for wheat and Tavakoli and Oweis (2004) and Webber et al (2006) for common green game bean.…”
Section: Water Productivity (Wp)supporting
confidence: 88%
“…WP values increased by 11.3 % and 2.9 %, respectively, when the A1/1E10 regime was applied to the (EFI15) and (A1/1C10) treatments. Similar findings were reported by Abdel-Maksoud et al (2002) for wheat and Tavakoli and Oweis (2004) and Webber et al (2006) for common green game bean.…”
Section: Water Productivity (Wp)supporting
confidence: 88%
“…Mineral fertilization with nitrogen was also reported to increase grain yield of maize. Abdel-Maksoud et al (2002); Shams (2000) and El-Murshedy (2002) reported that increasing N levels up to 105,120 and 140 kg N/fad., increased grain yield, number of rows/ear, number of grains/ row, 100 kernal weight and grain weight. These increases were attributed to the increase of yield attributes i.e.…”
Section: Introductionmentioning
confidence: 99%